Perancangan Mesin Pemotong Kertas Roll Otomatis dengan Metode Quality Function Deployment (QFD) - Yulianto, Risat Dwi; Alaika, Al Maida Nurul; Afrilio, Fajarayhan; Arya Pradana, Randyra Bagus; Prasetyo, Bagus Ari; Muslimin, Muslimin; Luqyana, Dhiya; Muhammad, Azam Milah (Manutech : Jurnal Teknologi Manufaktur, 2025)
This study focuses on the design of an automatic roll paper cutting machine using the Quality Function Deployment (QFD) method. The objective of this research is to develop a roll paper cutting tool capable of adjusting the length and quantity of cuts. The research was conducted by gathering customer requirements through interviews, analyzing technical characteristics, and structuring them using the Quality Function Deployment (QFD) method. Seven development priorities were identified through the creation of the House of Quality (HOQ), namely: (1) the width of the paper that can be cut, followed by (2) paper thickness, (3) power consumption, (4) cutting accuracy, (5) paper movement speed, (6) user interface (display), and (7) cutting time. The results of this study include a design concept for an automatic paper cutting machine that can adjust the length and quantity of cuts in accordance with product development priorities derived from customer requirement data.